Associations of health literacy with dental care use and oral health status in Japan - Keiko Murakami; Jun Aida; Shinichi Kuriyama; Hideki Hashimoto (BMC, 2023)
Abstract Background The concept of health literacy has gained prominence in the context of oral health. In Japan, curative dental care is generally under universal health coverage, while preventive dental care requires effort. We used this situation to test the hypothesis that high health literacy is associated with preventive dental care use and good oral health status, but not with curative dental care use, in Japan. Methods A questionnaire survey was conducted from 2010 to 2011 among residents aged 25-50 years in Japanese metropolitan areas. Data from 3767 participants were used. Health literacy was measured using the Communicative and Critical Health Literacy Scale, and the total score was categorized into quartiles. Poisson regression analyses with robust variance estimators were conducted to examine the associations of health literacy with curative dental care use, preventive dental care use, and good oral health, adjusted for covariates. Results The percentages of curative dental care use, preventive dental care use, and good oral health were 40.2%, 28.8%, and 74.0%, respectively. Health literacy was not associated with curative dental care use; the prevalence ratio (PR) of the highest relative to the lowest quartile of health literacy was 1.04 (95% confidence interval [CI], 0.93-1.18). High health literacy was associated with preventive dental care use and good oral health; the corresponding PRs were 1.17 (95% CI, 1.00-1.36) and 1.09 (95% CI, 1.03-1.15), respectively. Conclusions These findings may provide clues for the design of effective interventions to promote preventive dental care use and improve oral health status.